2007
DOI: 10.3354/dao01825
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological determinants in outbreaks of bitter crab disease (Hematodinium sp.) in snow crabs Chionoecetes opilio from Conception Bay, Newfoundland, Canada

Abstract: Bitter crab disease (BCD) is caused by Hematodinium sp., an endoparasitic dinoflagellate. It lives within the hemocoeloms of snow crabs Chionoecetes opilio and Tanner crabs C. bairdi, making them unmarketable due to their bitter flavor. Two recent outbreaks of BCD have occurred in Conception Bay, Newfoundland, one from 1999 to 2000 and another from 2003 to 2005. In the earlier outbreak, prevalence was highest in juvenile and primiparous females and juvenile males. It was thought to be highest in these hosts be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 35 publications
1
41
2
Order By: Relevance
“…in other host species has long been associated with moulting (Meyers et al 1987, 1990, Eaton et al 1991, Field et al 1992, Dawe 2002, 2007. The main moulting period for brown crabs in Irish fisheries occurs from September to December (Tully et al 2006), coinciding with high infection intensities observed in Q4 in the present study.…”
Section: This Is the First Report Ofsupporting
confidence: 64%
“…in other host species has long been associated with moulting (Meyers et al 1987, 1990, Eaton et al 1991, Field et al 1992, Dawe 2002, 2007. The main moulting period for brown crabs in Irish fisheries occurs from September to December (Tully et al 2006), coinciding with high infection intensities observed in Q4 in the present study.…”
Section: This Is the First Report Ofsupporting
confidence: 64%
“…It is distinctly possible that infections are transmitted during the molting of the host. This is a relatively common occurrence in diseases such as this, albeit not well documented except for rhizocephalan infections in crabs and some protozoal infections in crabs and lobsters (Tindle et al 2004, Shields et al 2007). Because crayfish were collected in nature, however, we acknowledge the possibility that wild-caught individuals may also vary in infection or disease susceptibility.…”
Section: Discussionmentioning
confidence: 95%
“…These estimates represent average natural mortality over the lifetime of a female and are lower than ours, which represent natural mortality of a female after terminal molt only. Prominent causes of natural mortality for pre-adult and adult females include fish predators such as skates and cod (Robichaud et al 1991, Chabot et al 2008) and in some areas (but not the northern Gulf of St. Law rence) bitter crab disease (Shields et al 2007, Mullow ney et al 2011. However, natural mortality rates of adult females may be higher on average than those of preadult females because of density-dependent sexual conflicts arising during the female's first mating period, which is intimately associated with terminal molt ; see Adler & Bondiuransky 2011 for more general considerations on sex ratio, density and the rate of ageing).…”
Section: Discussionmentioning
confidence: 99%